Citoyenneté, droit pénal et procédures pénale et civile à Ptolémaïs sous les Lagides - Matthieu Vallet (Droit et Cultures, 2016)
The Greek city-state of Ptolemais was settled by Ptolemy I Soter at the end of the fourth century BC. This new foundation in Upper-Egypt required Greek settlers, buildings, civic institutions and most of all, constitution and laws. Unfortunately only a few scraps of these laws are known. Nevertheless, Greek inscriptions and papyri from the third and second century BC allow us to observe the integration of the city in the legal system progressively built by the first Ptolemies. This system is particularly characterized by its pluralism and by the multiplicity of law sources (royal willpower, Egyptian customs, legal practices among Greek settlers, ethnical minorities’ traditions and civic institutions). The city’s ability to adopt laws, the attestation of civic criminal laws and procedures, the Ptolemais’ magistrates’ commitment in legal conflicts resolution and the relationships between these elements and the royal agents are the object of the following study. This study is based on the careful analysis of different particular examples of criminal and civil cases from the third and second centuries BC in which the civic institutions are involved.